High-Performing Polycarbazole Derivatives for Efficient Solution-Processing of Organic Solar Cells in Air - Burgués-Ceballos, Ignasi; Hermerschmidt, Felix; Akkuratov, Alexander V.; Susarova, Diana K.; Troshin, Pavel A.; Choulis, Stelios A. (My University, 2015)
The application of conjugated materials in organic photovoltaics (OPVs) is usually demonstrated in lab-scale spin-coated devices that are processed under controlled inert conditions. Although this is a necessary step to prove high efficiency, testing of promising materials in air should be done in the early stages of research to validate their real potential for low-cost, solution-processed, and large-scale OPVs. Also relevant for approaching commercialization needs is the use of printing techniques that are compatible with upscaling. Here, solution processing of organic solar cells based on three new poly(2,7-carbazole) derivatives is efficiently transferred, without significant losses, to air conditions and to several deposition methods using a simple device architecture. High efficiencies in the range between 5.0 % and 6.3 % are obtained in (rigid) spin-coated, doctor-bladed, and (flexible) slot-die-coated devices, which surpass the reference devices based on poly[N-9′-heptadecanyl-2,7-carbazole-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole)] (PCDTBT). In contrast, inkjet printing does not provide reliable results with the presented polymers, which is attributed to their high molecular weight. When the device area in the best-performing system is increased from 9 mm2 to 0.7 cm2, the efficiency drops from 6.2 % to 5.0 %. Photocurrent mapping reveals inhomogeneous current generation derived from changes in the thickness of the active layer.
Keywords: Copolymers; Photovoltaics; Solar cells; Solution processing; Upscaling